Efektifitas Penggunaan Skin Wrap dalam Mengatur Suhu Tubuh Pada Bayi Baru Lahir di Bagian Perinatologi Rumah Sakit Awal Bros Batam - Indah Purnama Sari; Annisa Putri Ridhanty (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Newborns can experience hypothermia shortly after birth, hypothermia occurs through several mechanisms, namely related to the body's ability to balance between heat production and heat loss. Failures caused by a decrease in the baby's body temperature drop by about 0.30C per minute. There are several ways to avoid hypothermia, including using skin wrap. Skin wrap is a plastic bag to reduce heat loss due to evaporation so that it is easy to increase the baby's temperature. The method of using skin wrap can be used to prevent hypothermia in neonates, both premature and non-premature. Hypothermia in infants can worsen the condition of babies who lose heat after birth. This study aims to determine the effectiveness of the use of skin wrap in regulating body temperature in newborns in the Peristi Room of Awal Bros Hospital Batam. The research method used is a quasi-experimental method with a pretest and posttest design with a sample of 20 respondents. The sampling method used purposive sampling technique, the instrument used was the SOP for the use of skin wrap and observation sheets. Based on the Shapiro-Wilk statistical test analysis, a p-value of 0.000 was obtained with results > 0.05, which means that there is an effective use of skin wrap in increasing body temperature in newborns.